A Comparison of Cognitive and Everyday Functional Performance among Older Adults With and Without Hypertension - Hudak, Elizabeth M. (2013)
Secondary data analyses examined the differences in cognitive and instrumental activities of daily living (IADL) performance among hypertensive individuals taking one of four classes of antihypertensive medications, hypertensive individuals not taking any antihypertensive medications, and normotensive individuals (N=770). After adjusting for covariates, significant group differences were evident on all measures (speed of processing, motor speed, reaction time, ps < .05) except memory and Timed IADL (ps > .05). Follow-up a priori planned comparisons compared hypertensive individuals not on medications to each of the four antihypertensive medication groups. Results indicated that only those on beta blockers (BB) were significantly slower in speed of processing (ps < .05). A priori planned comparisons also revealed that normotensive individuals had better cognitive performance on measures of processing speed, motor speed, and reaction time than hypertensive individuals regardless of antihypertensive medication use. Additionally, normotensive individuals performed significantly better on memory (Digit and Spatial Span) than individuals with hypertension on medications. No differences were found between groups on memory (Hopkins Verbal Learning Test) or Timed IADL performance. With regard to antihypertensive medications, the use of BBs was associated with slowed processing speed. These analyses provide empirical evidence that hypertension primarily impacts speed of processing, but not severe enough to affect IADL performance. Given the contribution of processing speed to memory and executive function performance, this is an important finding. Clinicians need to take into consideration the potential negative impact that BBs may have on cognition when determining the best treatment of hypertension among older adult patients.